Research funding and modes of knowledge production : a comparison between NRF-funded and industry-funded researchers in South Africa - Luruli, Ndivhuwo Mord (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.